Representations of the Black subject in Irma Stern's African periods : Swaziland, Zanzibar and Congo 1922-1955 - Kellner, Clive (Michaelis School of Fine Art, 2015)
This dissertation explores the major themes of Irma Stern's (1894-1966) representation of the black figurative subject in her African periods: Swaziland, Zanzibar and Congo (1922-1955). Germane to these periods are Stern's childhood experience in the Transvaal and her training and influences in Germany. My research aims to do the following: (1) address a gap in the current literature on Irma Stern and her African periods (2) to consider whether Stern's mature periods, Zanzibar and Congo reveal an imaginary 'primitivist' mode of representation. Central to my research is the question of Stern's identity as a woman, settler and Jew, as it is critical to exploring the relation between Stern as a white settler and that of her black figurative subjects as viewed through the discourse of 'primitivism'. My methodology involves drawing from various archives, primary and secondary literature on Stern and Stern's own writings. My visual methodology includes a comparative analysis of Stern's early paintings in relation to her influences and formal and iconographic analysis of select 'mature' paintings.